Instabilidade e incerteza: curva IS com dados de longo prazo - Dionísio Dias Carneiro; Thomas Yen Hon Wu (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2003)
– The IS Curve is the tool with which economists evaluate the restrictive impact of the interest rate on the GDP. This paper presents an estimate of the IS Curve for the Brazilian economy that incorporates data since 1980, that is, also covering the high inflation period. Two undesirable consequences require special attention when we consider this larger sample period. First, the switch in the regime might represent different data generating processes (problem known as structural break). Another effect is a change in the statistical precision with which coefficients can be estimated, consequence of the heterogeneity in the variance of the residuals (a problem called heteroskedasticity). Once these potential problems are controlled, this exercise becomes relevant since, as we will show later, empirical analysis that include in their sample period only data after the beginning of the Real Plan (that is, of the stabilized economy) fail to capture the influence of variables of unquestionable theoretical importance. We illustrate this point by analyzing the effect of the external environment on the internal growth, emphasizing the export channel.
Keywords: 330; IS-LM-Modell; Brasilien